Policy Considerations for Improving Influenza Vaccination Rates among Pregnant Women. Issue 3 (6th January 2014) - Mollard, Elizabeth K.; Guenzel, Nicholas; Brown, Peggy A.; Keeler, Heidi J.; Cramer, Mary E.
Abstract Background Influenza exposure during pregnancy can cause severe health problems for both the mother and her offspring, including an increased risk of mortality. Influenza vaccination during all trimesters of pregnancy is safe and effective, and recommended by professional organizations such as the American College of Obstetrics and Gynecology. Despite these recommendations, the U.S. vaccination rates remain low in this high‐risk population. Method A policy analysis based on the five‐part method identified by Teitelbaum and Wilensky (2013) addresses factors to consider in identifying the best voluntary policy options to improve the vaccination rates. The authors provide discussion of the background, landscape, and stakeholder interests and the pros and cons of two voluntary policy options to increase vaccination. The policy options include: (a) financial incentives for providers and (b) an education emphasis for providers and staff. Conclusions The authors conclude that based on considerations of cost, provider preference, and practicality of implementation, a continuing educational intervention is the preferred policy venue to increase vaccination rates.